Veterinary medicine and animal care in ancient Maghreb - BAMEBAREK REKIA, BAMEBAREK REKIA; BENABDELMOUMENE, Mohammed (The International tax journal, 2025)
Veterinary medicine, or more accurately animal medicine during the period under study, is considered one of the fundamental branches of medicine. It works to protect animals and maintain their health and treat injuries. It also plays a part in preventing humans from contracting diseases that can be transmitted through infection, as well as combatting pandemics and diseases that could have a devastating effect on the environment. This research paper aims to clarify the history of veterinary medicine and its role in various ancient civilisations, leading to the Maghrebi cultures. It begins by emphasising the importance of wild and domestic animals, drawing on sources that cover animal care and treatment methods.